A Survey Analysis Comparing Perceptions of Plastic Use in Nurseries and Greenhouses in the United States - Alexa J. Lamm; James S. Owen; James Altland; Sarah A. White (Land, 2025)
Plastic is extensively used in nursery and greenhouse operations. Concerns are growing about the potential release of plastic byproducts, such as microplastics and per- and poly-fluoroalkyl substances (PFAS), into water resources. The purpose of this study was to (1) compare perceptions of plastic use and water quality impacts between scientists researching water contaminants and nursery/greenhouse growers, (2) identify barriers to growers reducing plastic use, and (3) explore preferred communication channels for scientists to inform growers about emerging research. An online survey was administered to collect data from scientists in a USDA-funded multi-state Hatch project (N = 20) and nursery/greenhouse growers (N = 66) across the United States. The findings indicated both groups were unsure of the impacts of plastic use. While most respondents perceived surface water pollution as a critical issue, neither scientists nor growers strongly agreed on-farm plastic use poses a significant threat. Both groups recognized the importance of regular water testing, but few believed mandatory changes to plastic use should be enacted without further evidence. Growers cited limited equipment, financial constraints, and uncertain availability of viable plastic alternatives as key barriers. Despite these barriers, growers were willing to learn more, primarily through online resources, short courses, and workshops. The findings underscore the need for targeted research that quantifies plastic byproducts in nursery/greenhouse water and identifies cost-effective alternatives. Timely dissemination of scientific findings using trusted sources will be critical to bridge knowledge gaps and support adoption of best practices to safeguard water quality in surface and groundwater.